Research on the Development of School-Based Music Education Based on Ancient Poetry and Art Songs - Fu, Qiang (Journal of Educational Theory and Practice, 2026)
In order to enhance the cultural connotation and aesthetic value of music education and promote the inheritance and development of ancient poetry, art songs, this article focuses on the development of school-based curriculum. Ancient poetry and art songs combine the dual artistry of literature and music, and have unique cultural inheritance and aesthetic education functions, but they have not yet been fully valued in current music education. This article uses methods such as literature research, case analysis and action research to systematically explore the educational value of ancient poetry and art songs, analyze the current situation and problems of related curriculum development at home and abroad, and build a complete school-based curriculum system on this basis, including curriculum objectives, content design, teaching methods and evaluation mechanisms. Research has found that this course can effectively improve students’ aesthetic literacy, cultural identity and musical expression, while providing a new practical path for teachers’ professional development. Practice shows that the implementation of the curriculum enhances students’ interest in traditional culture and optimizes the teaching effect of music classes, but there are also challenges in resource integration and teacher training. Future research can further explore the long-term mechanism of the curriculum and the possibility of interdisciplinary integration.